PERAN CORPORATE SOCIAL RESPONSIBILITY DALAM TANGGUNGJAWAB LINGKUNGAN DI INDONESIA - Hikmat Syahputra Tarigan; Abdul Aziz Manurung; Danarzi Danarzi (Smart Education, 2025)
Abstract: Corporate Social Responsibility (CSR) is currently the most talked about topic in various places, both in formal and informal forums. The UN with its Global Compact is actively involved in discussing and supporting Corporate Social Responsibility (CSR) as an effort to contribute to creating welfare for the world community. More theoretically and systematically, the concept of the corporate social responsibility pyramid developed by Archie B. Carrol provides a logical justification for why a company needs to implement CSR for the surrounding community. CSR is a commitment from a company or the business world to contribute to developing a sustainable economy by paying attention to corporate social responsibility and emphasizing the balance between attention to economic, social and environmental aspects. The formulation of the problem is How is the Role of Corporate Social Responsibility in Environmental Responsibility in Indonesia. What are the obstacles in Corporate Social Responsibility in Environmental Responsibility in Indonesia? CSR is applied as a concept because it is expected to be able to provide an alternative path for new breakthroughs in empowering the poor, but the company has not been able to empower the poor or in other words has not been able to empower the poor. The budget is a factor that influences an activity that cannot be carried out properly as planned in advance. This factor can be influenced by both the company itself and those related to the company's involvement. Keywords: Responsibility; Environment Abstrak: Corporate Social Responsibility (CSR) saat ini menjadi bagian yang paling hangat dibicarakan diberbagai tempat, baik di forum formal maupun informal. PBB dengan Global Compact-nya terlibat aktif membahas dan mendukung Corporate Social Responsibility (CSR) sebagai upaya turut menciptakan kemaslahatan masyarakat dunia. Secara lebih teoritis dan sistematis, konsep piramida tanggung jawab sosial perusahaan yang dikembangkan Archie B. Carrol memberi justifikasi logis mengapa sebuah perusahaan perlu menerapkan CSR bagi masyarakat di sekitarnya. CSR adalah komitmen perusahaan atau dunia bisnis untuk berkontribusi dalam mengembangkan ekonomi yang berkelanjutan dengan memperhatikan tanggung jawab sosial perusahaan dan menitik beratkan pada keseimbangan antara perhatian terhadap aspek ekonomi, sosial dan lingkungan. Adapun rumusan masalahnya yaitu Bagaimana Peran Corporate Social Responsibility Dalam Tanggung jawab Lingkungan Di Indonesia. Bagaimana kendala dalam Corporate Social Responsibility Dalam Tanggung jawab Lingkungan Di Indonesia CSR diterapkan sebagai suatu konsep karena diharapkan mampu memberikan jalan alternatif terobosan baru dalam pemberdayaan masyarakat miskin, namun perusahaan belum mampu memberikan pemberdayaan masyarakat miskin atau dengan kata lain belum bisa memberdayakan masyarakat miskin. Anggaran merupakan faktor mempengaruhi suatu kegiatan tidak dapat terlaksana dengan semestinya yang telah direncanakan pada sebelumnya. Faktor ini bisa dipengaruhi baik dari perusahaan itu sendiri maupun yang menyangkut keterlibatan perusahaan. Kata kunci: Tanggung jawab; Lingkungan